Strategi Relationship Marketing dalam Meningkatkan Loyalitas Nasabah Pada Bank BRI Unit Muara Rupit - Yuyun Nomary; Hendra Sastrawinata; Keti Purnamasari (Jurnal Aplikasi Manajemen dan Bisnis, 2021)
One way to increase customer satisfaction and loyalty is to build a relationship between the bank and the customer which is called relationship marketing. This study aims to determine the direct and indirect effect of Relationship marketing variables and customer satisfaction on customer loyalty. Bank BRI Unit Muara Rupit is a bank that has been established in the Muara Rupit area on February 7, 1970 until now. This study used a sample of 95 respondents. The results showed that Relationship marketing and customer satisfaction had a positive and significant effect on customer loyalty. Relationship marketing variable has a dominant influence on customer loyalty at Bank BRI Muara Rupit Unit.